Paediatric Audiological Medicine. - Newton, Valerie E. (John Wiley & Sons, 2009)
Professionals will find a wide range of topics relevant to their work with hearing impaired children or those suspected of having an impairment in this book. A chapter on epidemiology includes the prevalence of hearing impairment and several additional chapters are devoted to the various causative factors. Detection of a hearing loss, measurement of the degree of hearing loss and identification of the site of lesion are covered together with management of any hearing loss found. Individual chapters give coverage to balance disorders, tinnitus, progressive hearing loss, auditory neuropathy, cen.